(untitled) (Proceedings of the International Conference on Education, 2021)
Coronavirus change the world included teaching approaches. With schools closed, technology has become a powerful tool for educational purposes; the potential of e-learning affects education significantly as it provides improved informational content and interactive apps to apply theoretical knowledge. Teaching methods should be considered for each subject to ensure students get significant experience. This paper summarizes findings from an empirical study involving a new integrated e-learning method for the architecture structural design course using flipping the classroom and gamification as learning methods. The e-learning solutions used were short videos containing each subject’s essential theory and interactive software programmed as smartphone applications containing the course subjects. A web site with the class videos embedded and examples for solving the application’s games ensures students get the same information and practice the same exercises. A comparison between classes on-site and online classes is presented to assess this new method’s effects. Results were promising; students like to learn about the class subjects at their own pace; they enjoyed practicing mathematical and physics theory feeling inside a video game mood. Students gained motivation, engagement, and good grades during this online learning period; no final exam